Tuberculosis/HIV co-infection in Brazilian state capitals: comments from the data of the Information System of Notifiable Diseases - Helder Oliveira e Silva; Marcelo Luiz Carvalho Gonçalves (Universidade de Fortaleza, 2009)
Objective: To describe the frequency of requests for serological testing for HIV infection in patients with Tuberculosis and the prevalence of such co-infection in Brazilian state capitals and in the Federal District (DF), between 2004 and 2006. Methods: It was a retrospective epidemiological survey based in the data of Brazil's Information System of Notifiable Diseases (SINAN). The data were collected in August, 2008. In the studied period, there were notified in SINAN, 35,639 cases of Tuberculosis in 2004, 37,520 in 2005 and 34,439 in 2006, in all the 26 state capitals and the DF. The percentage of patients with known serological status and the percentage of patients with positive testing for HIV infection within the patients with Tuberculosis varied widely among the capitals and among the time periods assessed. Results: The municipalities of Rio Branco and Macapá (North region) showed the worse coverage of serological testing for HIV infection, with a frequency of not screening above 86.5% in the three years of the study. The best HIV screening coverage occurred in Campo Grande (Center-West region) and Curitiba (South region), with frequencies of not testing fewer than 20.5%. The frequency of Tuberculosis/HIV co-infection varied from 64.5% in Florianópolis (South region), in 2004 to 0% in Rio Branco (North region), in 2006. Conclusion: In the study, the regional disparities for HIV serological testing in patients with Tuberculosis were observed. In order to achieve the goals for HIV screening in all patients with Tuberculosis there shall be necessary some operational adjustments and a greater commitment in the implantation of public policies directed for these populations.